2016
DOI: 10.1016/j.jaci.2016.01.035
|View full text |Cite
|
Sign up to set email alerts
|

T-helper signals restore B-cell receptor signaling in autoreactive anergic B cells by upregulating CD45 phosphatase activity

Abstract: Our findings suggest that CD45 is a key regulator of BCR-signaling thresholds mediated by T-cell help. This raises the possibility that BND cells could represent precursors of autoantibody-secreting plasma cells and suggests a role for these autoreactive B cells in contributing to autoimmunity if not properly controlled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 49 publications
3
34
0
Order By: Relevance
“…Before these results were obtained, it has been reported that Th2 signals restore BCR signalling in a small population of anergic IgM-IgD+-naïve B cells present in blood of healthy donors and patients with SLE. 92 IL-4 or IL-21 alone led to modest effects on the pSyk(Y352) response to BCR engagement. IL-4 in combination with CD40L, however, led to higher responses than with CD40L alone.…”
Section: Co-stimulation Of Cd40 Effectively Improves B Cell Anergy Inmentioning
confidence: 93%
“…Before these results were obtained, it has been reported that Th2 signals restore BCR signalling in a small population of anergic IgM-IgD+-naïve B cells present in blood of healthy donors and patients with SLE. 92 IL-4 or IL-21 alone led to modest effects on the pSyk(Y352) response to BCR engagement. IL-4 in combination with CD40L, however, led to higher responses than with CD40L alone.…”
Section: Co-stimulation Of Cd40 Effectively Improves B Cell Anergy Inmentioning
confidence: 93%
“…Anergic B cells are considered a source of self-reactive ASCs in SLE as they can persist in the mature B cell repertoire and interact with T h cells [37][38][39]; however, the exact mechanism by CXCR5 -PD-1 hi T cells. Graphs for (D), (E), (G), (I) and (J) show the proportions of T fh , T fr , CXCR5 -PD-1 hi T, T eff and T reg cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Anergic B cells are considered a source of self-reactive ASCs in SLE as they can persist in the mature B cell repertoire and interact with T h cells [ 37 39 ]; however, the exact mechanism by which anergic B cells convert to ASCs–and whether or not they are the true drivers of autoAb production–remains unclear. In this study, we found that NZB c1 lupus-prone congenic mice can breach tolerance to nuclear antigen, but that this is severely attenuated in the Vκ8/3H9 anergic model, with limited production of autoAbs despite high numbers of ssDNA-reactive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, oligomerized sCD40L was ineffective in a large majority of our "in vitro" experiments. Due to its effectiveness in B-cell activation, [52][53][54][55] the original CD40-mediated functional assay, oligomerized s40L is usually considered as the reference standard for CD40 triggering tests. However, the extent of CD40 polymerization has been shown to critically affect the elicitation of the multiplicity of functional effects induced by its triggering.…”
Section: Discussionmentioning
confidence: 99%